Eksistensi dan Perkembangan ISIS: Dari Irak Hingga Indonesia - Najamuddin Khairur Rijal (Jurnal Ilmiah Hubungan Internasional, 2017)
This article examines the development of the Islamic State of Iraq and Syria (ISIS) as the local movement in Iraq into a transnational movement until spreading in Indonesia. The explanation focused on the historical development of ISIS from time to time and then have contact with Islamic revivalism group in Indonesia. The aspire of ISIS is to establish an Islamic caliphate in Iraq and Syria. In an effort to realize its objectives, ISIS spreading its ideology through various propaganda to attract followers from many countries. In Indonesia context, the inclusion of ISIS not be separated from contact with the Islamic revivalism groups that previously have long been present in Indonesia. Early development of the network and ISIS sympathizers in Indonesia was marked by the release of a video on Youtube titled “Join the Ranks”, hereinafter the government responded by banning ISIS either formally or informally because ISIS ideology incompatible with Pancasila and the condition of diversity in Indonesia.